The Role of Playing Model Learning Based on Tri Hita Karana Improve Indonesian Language Learning Outcomes - Trisnawati, Komang; Yuda Sukmana, Adrianus I Wayan Ilia (Universitas Pendidikan Ganesha, 2020)
This study aims to determine the effect of the Tri Hita Karana-based Role-Playing type of cooperative learning model on Indonesian language learning outcomes. This research is a quasi-experimental study with a non-equivalent post-test only control group design. The population of this study was 177 people, the sample was determined using simple random sampling. The sample of this research was 28 students in class IV SD 1 Banjar Tegal and 28 students in class IV SD 1 Baktiseraga as many as 28 people. Indonesian learning outcomes data obtained through the method of providing multiple choice tests. Based on the results of hypothesis testing shows that there are significant differences in Indonesian learning outcomes between groups of students who are taught with a cooperative learning model based on Tri Hita Karana type and students who are not taught using the cooperative learning model based on Tri Hita Karana. Thus, the cooperative learning model of the type of Role Playing based on Tri Hita Karana because it affects the learning outcomes of Indonesian students. Based on the results of the study, it is recommended that this study can be used as a support or relevant study in subsequent studies to fund a type of cooperative learning model based on Tri Hita Karana.